HUBUNGAN PEMANFAATAN MODAL SOSIAL PETANI DENGAN PERILAKU USAHATANI PADI SAWAH DI KECAMATAN BATANG ASAM KABUPATEN TANJUNG JABUNG BARAT - Rendra, Rendra (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2018)
This research aims to increase the attention of various parties on the importance of social capital owned by the farming community, especially rice farmers and in the future it is hoped that a model can be developed in developing social capital as a potential and strategy for agricultural development activities in the future. in the context of farmer community empowerment activities.In the short term it is expected to know and identify the various social capital owned and how much social capital is owned by the farming community and to find out how it relates to the farming behavior.The method used is to use a combination of qualitative (descriptive) and quantitative methods. The research data were obtained from observations and interviews (in-depth interviews and structured interviews). The data obtained will be processed statistically using Chi-Square analysis. This research will be carried out in half a year or in one wetland rice planting season. This research will be very useful for the government and private sector as well as NGOs' who are directly involved in carrying out empowerment activities to the community. For academics is also an important point in developing models for improving the welfare of the farming community in the future.